2023
DOI: 10.3390/ani13081274
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effects of the Combination of L-Carnitine and Lycopene on the Lycopene Bioavailability and Duodenal Health of Roosters

Abstract: The objective of this study was to investigate the impact of Lycopene and L-Carnitine, individually or in combination, on various physiological and molecular factors related to intestinal health and absorption ability in Roosters, such as intestinal morphology, serum biochemical parameters, genes involved in Lycopene uptake, nutritional transport genes, and tight junction genes. The findings of the study revealed that the combination of L-Carnitine and Lycopene supplementation had been found to increase the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…For fixed tissues, hematoxylin and eosin staining was performed ( 34 ) followed by microscopic observation and image processing and analysis system (Version 1, Leica Imaging Systems Ltd, Cambridge, UK). Villus height (VH, μm), crypt depth (CD, μm), and villus width (VW, μm) measurements were performed from 3 different regions of each section (with intact villi and straight orientation), and the average values were taken as the measurement results ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…For fixed tissues, hematoxylin and eosin staining was performed ( 34 ) followed by microscopic observation and image processing and analysis system (Version 1, Leica Imaging Systems Ltd, Cambridge, UK). Villus height (VH, μm), crypt depth (CD, μm), and villus width (VW, μm) measurements were performed from 3 different regions of each section (with intact villi and straight orientation), and the average values were taken as the measurement results ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacological effects of natural metabolites have drawn an enormous amount more attention in recent years ( Pan et al, 2019 ). Clinical data and in vitro studies have shown the beneficial effects of natural products on a wide range of diseases ( Ennab et al, 2019 ; Mustafa et al, 2019 ; Ullah et al, 2020 ; Ennab et al, 2023 ). These changes in the gut microbiota caused by natural substances demonstrate that natural products have a preventive effect on the development of inflammation into cancer.…”
Section: Effect Of Natural Products On Gut-x Axis (Pharmacology Toxic...mentioning
confidence: 99%
“…Histological analysis was carried out in accordance with previous research [43][44][45][46][47]. The tissues were first dehydrated using a graded series of ethanol and xylene, followed by paraffin wax clearing and infiltration.…”
Section: Histologic Assessmentmentioning
confidence: 99%